An analysis of genetic stock identification on a small geographical scale using microsatellite markers, and its application in the management of a mixed‐stock fishery for Atlantic salmon Salmo salar in Ireland. Issue 6 (14th May 2013) - Ensing, D.; Crozier, W. W.; Boylan, P.; O'Maoiléidigh, N.; McGinnity, P.
<x xml:space="preserve">Abstract</x> A genetic stock identification (GSI) study was undertaken in a fishery for Atlantic salmon Salmo salar to determine the effects of restrictive fishery management measures on the stock composition of the fishery, and if accurate and precise stock composition estimates could be achieved on the small geographical scale where this fishery operates, using a suite of only seven microsatellite loci. The stock composition of the Foyle fishery was shown to comprise almost exclusively of Foyle origin fish in the 3 years after restrictive measures were introduced in 2007, compared to 85% the year before. This showed that the restrictive measures resulted in the Foyle fishery being transformed from a mixed‐stock fishery to an almost exclusively single‐stock fishery, and showed how GSI studies can guide and evaluate management decisions to successfully manage these fisheries. Highly accurate and precise stock composition estimates were achieved in this study, using both cBAYES and ONCOR genetic software packages. This suggests accurate and precise stock composition is possible even on small geographical scales.